IDENTIFICATION AND ASSESSMENT OF RISK FACTORS THAT CONTRIBUTE TO THE FORMATION OF CHRONIC CONSTIPATION IN THE ADULT POPULATION - Мусаєв, Р.Г. (World of Medicine and Biology, 2016)
Goal. The study by questionnaire and mobile health features of the chronic constipation (CC) prevalence among the adult population of Baku, the identification of risk factors (RF), contributing to the formation of CC and socio-hygienic assessment. Methods. The survey was conducted using the SF-36 questionnaire, adapted to the purpose of the present study. BMI was determined by the Quetelet index, F - scale, GPAQ. All analyzed 2127 fully completed questionnaires, of which 1732 questionnaires were submitted by men, 395 questionnaires – women. Results. The set of questions questionnaire, reflecting the well-known symptoms of CC, affirmative 635 men (36,7±1,2%) and 163 women (41,8±2,5%; t=1,66; p>0.05). With increasing age, the incidence of CC among men increased from 24.6±3.7 V to 45.2±3,7% (t=3,94; p
Keywords: medical negotiability; adherence to the treatment; population; chronic constipation